Comparative microbiome diversity in root-nodules of three Desmodium species used in push-pull cropping system - Adan, Isack H.; Asudi, George Ochieng; Niassy, Saliou; Jalloh, Abdul A.; Mutua, Johnstone Mutiso; Chidawanyika, Frank; Khamis, Fathiya; Khan, Zeyaur; Subramanian, Sevgan; Dubois, Thomas; Mutyambai, Daniel Munyao (Frontiers in Microbiology, 2024)
Background Desmodium species used as intercrops in push-pull cropping systems are known to repel insect-pests, suppress Striga species weeds, and shift soil microbiome. However, the mechanisms through which Desmodium species impact the soil microbiome, either through its root exudates, changes in soil nutrition, or shading microbes from its nodules into the rhizosphere, are less understood. Here, we investigated the diversity of root-nodule microbial communities of three Desmodium species- Desmodium uncinatum (SLD), Desmodium intortum (GLD), and Desmodium incanum (AID) which are currently used in smallholder maize push-pull technology (PPT). Methods Desmodium species root-nodule samples were collected from selected smallholder farms in western Kenya, and genomic DNA was extracted from the root-nodules. The amplicons underwent paired-end Illumina sequencing to assess bacterial and fungal populations. Results We found no significant differences in composition and relative abundance of bacterial and fungal species within the root-nodules of the three Desmodium species. While a more pronounced shift was observed for fungal community compositions compared to bacteria, no significant differences were observed in the general diversity (evenness and richness) of fungal and bacterial populations among the three Desmodium species. Similarly, beta diversity was not significantly different among the three Desmodium species. The root-nodule microbiome of the three Desmodium species was dominated by Bradyrhizobium and Fusarium species. Nevertheless, there were significant differences in the proportion of marker gene sequences responsible for energy and amino acid biosynthesis among the three Desmodium species, with higher sequence proportions observed in SLD. Conclusion There is no significant difference in the microbial community of the three Desmodium species used in PPT. However, root-nodule microbiome of SLD had significantly higher marker gene sequences responsible for energy and amino acid biosynthesis. Therefore, it is likely that the root-nodules of the three Desmodium species host similar microbiomes and influence soil health, consequently impacting plant growth and agroecosystem functioning.